Ajuste de las propiedades mecánicas de la madera estructural por cambios del contenido de humedad - Ordóñez Candelaria, V. Rubén; Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
The moisture content of wood, and its variation with atmospheric changes, is one of the factors with the greatest influence on wood properties. Therefore, it is necessary to know the degree to which mechanical properties vary as moisture content changes.  Using the results from research conducted by Madsen, and selecting the species most similar to Mexican pines in strength and density, expressions were derived to adjust the results obtained in the national study of the strength of coniferous wood. In this paper, we present the procedure used to obtain the adjustment expressions for bending, tension, compression parallel to grain and shear parallel to grain. Moisture content was adjusted to a uniform value in order to obtain comparable strength values for design.